2015
DOI: 10.1111/fwb.12542
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of isotopic niche widths of some invasive and indigenous fauna in a South African river

Abstract: 1. Biological invasions threaten ecosystem integrity and biodiversity, with numerous adverse implications for native flora and fauna. Established populations of two notorious freshwater invaders, the snail Tarebia granifera and the fish Pterygoplichthys disjunctivus, have been reported on three continents and are frequently predicted to be in direct competition with native species for dietary resources. 2. Using comparisons of species' isotopic niche widths and stable isotope community metrics, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 63 publications
0
46
1
2
Order By: Relevance
“…Dietary niche, as determined by variation in ÎŽ 13 C and ÎŽ 15 N, was most often broader in less successful invasive species of Cladoceran waterflea and oyster, but more successful species of tunicate. This inconsistency was contrary to our hypothesis of a universally broader isotopic niche in more successful aquatic invasive species, and contrasts with studies that have found broader dietary niches in the most widespread and dominant invasive species of fishes (GarcĂ­a‐Berthou ; Pettitt‐Wade et al ), reptiles (Reed et al ), birds, and mammals (Hayes and Barry ), and in aquatic invasive invertebrates compared to native aquatic invertebrates (e.g., Piscart et al ; Hill et al ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Dietary niche, as determined by variation in ÎŽ 13 C and ÎŽ 15 N, was most often broader in less successful invasive species of Cladoceran waterflea and oyster, but more successful species of tunicate. This inconsistency was contrary to our hypothesis of a universally broader isotopic niche in more successful aquatic invasive species, and contrasts with studies that have found broader dietary niches in the most widespread and dominant invasive species of fishes (GarcĂ­a‐Berthou ; Pettitt‐Wade et al ), reptiles (Reed et al ), birds, and mammals (Hayes and Barry ), and in aquatic invasive invertebrates compared to native aquatic invertebrates (e.g., Piscart et al ; Hill et al ).…”
Section: Discussioncontrasting
confidence: 99%
“…Insights on the breadth of resources consumed by invasive species in relation to invasion success and phenotypic traits can provide a template for predicting impacts to food web structure following establishment (Rudnick and Resh ). Yet, to our knowledge, this is the first study to compare the isotopic niche of the chosen species pairs of invasive oyster, Cladoceran waterflea and tunicate, and one of the few studies to compare isotopic niches of aquatic invasive invertebrates (but see Rudnick and Resh ; Jackson et al ; Jackson and Britton ; Rosewarne et al , comparisons in the third and fourth studies listed were between invasive fish and invasive crayfish), whereas comparison between native and invasive invertebrates is relatively common (e.g., Olsson et al ; Piscart et al ; Hill et al ; Karlson et al ; HerkĂŒl et al ). Ultimately, the findings of this research will provide for a better understanding of the mechanisms for survival across broad geographic ranges and to enhance trait based analysis for species distribution models and risk assessments.…”
mentioning
confidence: 99%
“…The success of invasive species is often attributed to their plasticity in behavior and diet choice (e.g., Sol et al 2002;Caut et al 2008). Invasive fishes often have higher feeding rates (Alexander et al 2014) and wider niche breadths (Carman et al 2006;Jackson and Britton 2013;Hill et al 2015) than native species which could explain their higher degree of niche overlap with spiders when compared to native fish. However, in streams where invasive trout are functionally redundant due to the presence of a functionally similar native fish, their impact on riparian consumers is likely to be undetectable.…”
Section: Discussionmentioning
confidence: 98%
“…; Jackson and Britton ; Hill et al. ) than native species which could explain their higher degree of niche overlap with spiders when compared to native fish. However, in streams where invasive trout are functionally redundant due to the presence of a functionally similar native fish, their impact on riparian consumers is likely to be undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…The subscript “c” indicates a small sample size correction (Jackson et al., ). All metrics were bootstrapped ( N = 10,000), so comparisons could be made between populations with differing sample sizes (minimum sample size N > 5, Hill, Jones, Hill, & Weyl, ; Jackson & Britton, ; Jackson et al, ). No fishes of the genus Labeo were sampled from the Kwando River, so this group was excluded from the Kwando River analysis.…”
Section: Methodsmentioning
confidence: 99%